2007
DOI: 10.1021/la701388w
|View full text |Cite
|
Sign up to set email alerts
|

Formation of “Snowmanlike” Polystyrene/Poly(methyl methacrylate)/Toluene Droplets Dispersed in an Aqueous Solution of a Nonionic Surfactant at Thermodynamic Equilibrium

Abstract: "Snowmanlike" polystyrene (PS)/poly(methyl methacrylate) (PMMA) composite particles were prepared by evaporation of toluene from PS/PMMA/toluene droplets dispersed in an aqueous solution of polyoxyethylene nonylphenyl ether surfactant (Emulgen 911). Partitioning experiments revealed that the Emulgen 911 concentration was higher in the droplets than in the aqueous solution during toluene evaporation. As a consequence, the interfacial tensions between the polymer phases (PS and PMMA) and the aqueous phase (gamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 48 publications
0
57
0
Order By: Relevance
“…Previous work 37 has shown that a non-ionic surfactant (polyoxyethylene nonylphenylether with an average ethylene oxide Preparation of hemispherical polystyrene particles T Tanaka et al chain length of 10.9) dissolved into both the oil and aqueous phases and significantly reduced the oil-aqueous medium interfacial tension. Figure 4 shows the variation of Emulgen concentrations in aqueous media as a function of the toluene weight fraction relative to the total amount of toluene, water and Emulgen.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work 37 has shown that a non-ionic surfactant (polyoxyethylene nonylphenylether with an average ethylene oxide Preparation of hemispherical polystyrene particles T Tanaka et al chain length of 10.9) dissolved into both the oil and aqueous phases and significantly reduced the oil-aqueous medium interfacial tension. Figure 4 shows the variation of Emulgen concentrations in aqueous media as a function of the toluene weight fraction relative to the total amount of toluene, water and Emulgen.…”
Section: Resultsmentioning
confidence: 99%
“…[36][37][38] It was revealed that the particle morphology could be controlled by tuning the interfacial tensions by varying the types of surfactant.…”
Section: Introductionmentioning
confidence: 99%
“…2A). This indicated that, despite the carboxylic charge derived from the V501 on the surface, Table 2 Ab-initio emulsion polymerizations of styrene or (butyl acrylate-co-methyl methacrylate) using Janus polystyrene nanoparticles which have V-501 derived cross-linked polystyrene seeds stabilized by RAFT-Sty 20 Scheme 3 Schematic behaviour of the monomer swollen cross-linked polymer seed on heating. The wetting ability of the monomer governs the morphology of the anisotropic particles formed during subsequent polymerization.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the fragmented nanosheets would be included in innovative anisotropic nanomaterials as proposed previously, e.g., inorganic nanosheets composed of graphene dissociated from graphite [30,31] and anisotropic polymer particles (discs- and snowman-like shapes, etc. ) fabricated by seeded dispersion polymerization [32,33]. …”
Section: Fabrication and Characterization Of Submillimeter-sized Nmentioning
confidence: 99%